Positive and negative aspects of Palliative Care in Perinatology and Neonatology from the perspective of a multi-professional team (Research, Society and Development, 2022)
Objetives: to identify positive and negative aspects in the palliative care assistance of pregnant women with detected fetal abnormalities and/or newborns with poor prognosis, according to the perception of a multidisciplinary team in a university hospital. Methods: descriptive study with a qualitative approach with professionals from the maternity unit, obstetric emergency room and neonatal intensive care unit. Data collection took place from June 2018 to May 2019, through semi-structured interviews. The Critical Incident Technique was used. Results: the study sample consisted of 56 professionals from the multidisciplinary team. 236 critical incidents emerged, 88 with positive aspects and 148 with negative ones. Conclusion: it was possible to identify a more significant number of negative references to the detriment of positive ones regarding palliative care, demonstrating that such approach involves more difficulties for its proper implementation. This study provided information that might enable the development of measures to improve palliative for this population and to promote a perinatal and neonatal palliative care group implementation with periodic training and education for the multidisciplinary team.